Continuous impinging in a two-stage micromixer for the homogeneous growth of monodispersed ultrasmall Ni–Co oxides on graphene flakes with enhanced supercapacitive performance. (4th May 2021) - Zhao, Junping; Wu, Yechao; Chen, Yihuang; Jin, Huile; Pan, Shuang; Zhao, Shiqiang; Feng, Xin; Wang, Yahui; Zhang, Qingcheng; Wang, Shun
Abstract : A two-stage microimpinging stream reactor (TS-MISR) strategy that combines a first homogeneous premixing stage with a subsequent microimpinging stream reacting stage has been constructed for the controllable synthesis of Ni–Co–O/RGO composites. Abstract : Sub-5 nm monodispersed metal oxides have been attracting much attention in energy storage due to their large electrolyte ion-accessible surface areas and high specific capacities. However, the high surface free energy of ultrasmall nanoparticles inevitably results in their serious aggregation, leading to degraded electrochemical activities and poor cycling stability. Herein, a two-stage microimpinging stream reactor (TS-MISR) strategy that combines a first homogeneous premixing stage with a subsequent microimpinging stream reacting stage has been constructed for the controllable synthesis of Ni–Co–O/RGO composites (NCG). Benefiting from the enhanced micromixing efficiency and better process control of TS-MISR, monodispersed ultrasmall Ni–Co–O particles (3–4 nm) are evenly grown on the RGO flakes to generate a large specific surface area (293.2 m 2 g −1 ), quantities of desirable mesopores (2–4 nm), as well as a strong synergistic effect between Ni–Co–O particles and conductive RGO flakes, hence providing more superficial electroactive sites, fast electron transfer and short diffusion paths for electrolyte ions to participate in faradaic redox reactions. The as-prepared NCG-MM exhibits a large specific capacity of 912.4 C g −1 (capacitance of 2281 F g −1 ) at the current density of 1 A g −1, good rate capability and cycling stability. Coupled with the activated carbon (AC) negative electrode, the assembled pouch-type NCG//AC asymmetric supercapacitor displays a prominent areal energy density (0.898 mW h cm −2 at 0.8 mW cm −2 ) and an excellent cycling stability (∼90.5% capacity retention after 8000 cycles). In addition, this strategy opens up an important prospect for the controllable synthesis of monodispersed metal oxide/graphene composites for application in batteries, sensors and catalysis.